The Formation of Indonesian and Japanese Affixal Negation - Maulia, Dini; Hariri, Tatang; Arimi, Sailal (Journal of Language and Literature, 2024)
There is still a lack of interest in researching affixal negation, especially among linguists, although the phenomenon of construction formation is interesting to explore. It has been understood that the negation dichotomy that Klima introduced is still commonly used in classifying the form of negation. It is classified into two forms: sentential and constituent negation. Based on Klima's negation dichotomy, it can be said that affixal negation is part of the subdomain in constituent negation. Indonesian and Japanese used the same strategy in constructing the affixal negation. Both languages use the negative prefix, which attaches to other constituents, to form the affixal negation construction. This research tries to explore and compare the process as well as the principles of forming the affixal negation in both Indonesian and Japanese. The main source of data used for this research is primarily taken from dictionaries and published articles related to negation. The comparison analysis is done using a theoretical contrastive analysis method to determine the contrast features and variables in Indonesian and Japanese affixal negation formation. The analyzed data shows that the borrowed affixes, change of sounds, word element, and derivation process are the main contrast features in affixal negation formation, especially in Indonesian and Japanese. In addition, the affixation process, role, and flexibility are the variable features during affixal negation formation in both languages.